Mentha cordifolia Leaf Extract Improves Hepatic Glucose and Lipid Metabolism in Obese Mice Fed with High-Fat Diet - Naowaboot, Jarinyaporn (Prev Nutr Food Sci, 2021)
Mentha cordifolia (MC) is a popular herb used to flavor food in Thailand that exhibits several biological effects. The present study aimed to determine the role of MC in regulating glucose and lipid metabolism in mice fed a high-fat diet (HFD). ICR obese mice were fed an HFD (45 kcal% lard fat) for 12 weeks, with MC (100 and 200 mg/kg/d) treatment from Week 7. After treatment with MC for 6 weeks, mice showed significantly lower rates of hyperglycemia, hyperinsulinemia, hyperleptinemia, and hyperlipidemia, and increased amounts of serum adiponectin. Furthermore, in mice treated with MC, serum interleukin-6 and tumor necrosis factor alpha were significantly inhibited and liver histology results showed decreased lipid accumulation and liver triglyceride content vs. untreated mice. In addition, MC treatment was associated with smaller fat cells and lower gene expression of liver sterol regulatory element binding protein 1c, acetyl-CoA carboxylase, and fatty acid synthase. However, MC treatment was associated with higher carnitine palmitoyltransferase 1a gene expression and significantly higher rates of adenosine monophosphate-activated protein kinase (AMPK) phosphorylation in liver, but lower levels of phosphoenolpyruvate carboxykinase and glucose-6-phosphatase. These results indicate MC regulates glucose and lipid metabolism in a HFD-induced obese mouse model, possibly via activation of AMPK signaling pathway.